Respostas
respondido por:
1
Olá, boa tarde!
Montando a expressão:
![\dfrac{2^{\frac{2}{3}}}{2}=2^{\frac{2}{3}-1}=2^{\frac{2}{3}-\frac{3}{3}}=2^{-\frac{1}{3}}=\sqrt[3]{2^{-1}}=\sqrt[3]{\frac{1}{2}} \dfrac{2^{\frac{2}{3}}}{2}=2^{\frac{2}{3}-1}=2^{\frac{2}{3}-\frac{3}{3}}=2^{-\frac{1}{3}}=\sqrt[3]{2^{-1}}=\sqrt[3]{\frac{1}{2}}](https://tex.z-dn.net/?f=%5Cdfrac%7B2%5E%7B%5Cfrac%7B2%7D%7B3%7D%7D%7D%7B2%7D%3D2%5E%7B%5Cfrac%7B2%7D%7B3%7D-1%7D%3D2%5E%7B%5Cfrac%7B2%7D%7B3%7D-%5Cfrac%7B3%7D%7B3%7D%7D%3D2%5E%7B-%5Cfrac%7B1%7D%7B3%7D%7D%3D%5Csqrt%5B3%5D%7B2%5E%7B-1%7D%7D%3D%5Csqrt%5B3%5D%7B%5Cfrac%7B1%7D%7B2%7D%7D)
Propriedades que nos garantem isso:
![\dfrac{a^n}{a^m}=a^{n-m}\\\\a^{\frac{n}{m}}=\sqrt[m]{a^n}\\\\a^{-n}=\dfrac{1}{a^n} \dfrac{a^n}{a^m}=a^{n-m}\\\\a^{\frac{n}{m}}=\sqrt[m]{a^n}\\\\a^{-n}=\dfrac{1}{a^n}](https://tex.z-dn.net/?f=%5Cdfrac%7Ba%5En%7D%7Ba%5Em%7D%3Da%5E%7Bn-m%7D%5C%5C%5C%5Ca%5E%7B%5Cfrac%7Bn%7D%7Bm%7D%7D%3D%5Csqrt%5Bm%5D%7Ba%5En%7D%5C%5C%5C%5Ca%5E%7B-n%7D%3D%5Cdfrac%7B1%7D%7Ba%5En%7D)
Espero ter ajudado.
Bons estudos! :)
Montando a expressão:
Propriedades que nos garantem isso:
Espero ter ajudado.
Bons estudos! :)
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
9 anos atrás